Data for Social Good Non-Profit Sector Data Projects - Farmer, Jane (Springer Nature, 2023)
This open access book provides practical guidance for non-profits and community sector organisations about how to get started with data analytics projects using their own organisations' datasets and open public data. The book shares best practices on collaborative social data projects and methodology. For researchers, the work offers a playbook for partnering with community organisations in data projects for public good and gives worked examples of projects of various sizes and complexity.